Investigations of the analytic and probabilistic number theory in Šiauliai University - Šiaučiūnas, Darius (Lietuvos matematikos rinkinys, 2010)
In this paper, the investigations of analytic and probabilistic number theory which were done in Šiauliai University are reviewed.
Keywords: Dirichlet series; limit theorem; multiplicative function; universality; weak convergence; zeta function